Mass Spectrometry–Based Lipidomics of Oral Squamous Cell Carcinoma Tissue Reveals Aberrant Cholesterol and Glycerophospholipid Metabolism — A Pilot Study - Dickinson, Amy; Saraswat, Mayank; Joenväärä, Sakari; Agarwal, Rahul; Jyllikoski, Daniel; Wilkman, Tommy; Mäkitie, Antti; Silén, Suvi (Translational Oncology, 2020)
Lipid metabolic reprogramming is one hallmark of cancer. Lipid metabolism is regulated by numerous enzymes, many of which are targeted by several drugs on the market. We aimed to characterize the lipid alterations in oral squamous cell carcinoma (OSCC) as a basis for understanding its lipid metabolism, thus identifying potential therapeutic targets. We compared lipid species, classes, and glycerophospholipid (GPL) fatty acid species between paired tumor tissue and healthy oral tongue mucosa samples from 10 OSCC patients using a QExactive mass spectrometer. After filtering the 1370 lipid species identified, we analyzed 349 species: 71 were significantly increased in OSCC. The GPL metabolism pathway was most represented by the lipids differing in OSCC (P =.005). Cholesterol and the GPLs phosphatidylcholines, phosphatidylethanolamines, and phosphatidylinositols were most significantly increased in OSCC tissue (FC 1.8, 2.0, 2.1, and 2.3 and, P =.003, P =.005, P =.002, P =.007). In conclusion, we have demonstrated a shift in the lipid metabolism in these OSCC samples by characterizing the detailed landscape. Predominantly, cholesterol and GPL metabolism were altered, suggesting that interactions with sterol regulatory binding proteins may be involved. The FA composition changes of the GPLs suggest increased de novo lipogenesis.
CRIS-Team Scopus Importer:2020-06-23